Ten-year long-term organic fertilization enhances carbon sequestration and calcium-mediated stabilization of aggregate-associated organic carbon in a reclaimed Cambisol - Huang, Xiaolei; Jia, Zhixin; Guo, Junjie; Li, Tingliang; Sun, Dasheng; Meng, Huisheng; Yu, Guanghui; He, Xinhua; Ran, Wei; Zhang, Shusheng; Hong, Jianping; Shen, Qirong (Geoderma, 2019)
Soils play a vital role in the global carbon (C) cycle, yet little is known about the calcium (Ca)-mediated stabilization of soil organic carbon (SOC) in calcareous soils. With wet sieving, density fractionation and an incubation experiment from field soils, we investigated the effects of long-term fertilization on the Ca-mediated stabilization of aggregate-associated organic C and on the SOC stock at a soil depth of 0–20 cm in a reclaimed Cambisol on the Loess Plateau of China. Compared to the initial soil, after ten years the SOC stock increased by 50%, 76%, 94% and 110% in soils amended with no fertilizer (control), 100% chemical fertilizer, 50% chemical fertilizer plus 50% chicken manure compost and 100% chicken manure compost, respectively. The specific C mineralization rate (SCMR, rate per unit SOC) decreased as silt and clay > macroaggregate > microaggregate, indicating that SOC in microaggregates was more stable than in macroaggregates and the silt and clay fraction. The exchangeable Ca in the bulk soil (P < 0.001) and soil aggregates (P < 0.001) were positively correlated with the SOC, whereas the Ca carbonate (CaCO3) was negatively correlated with the SCMR (P < 0.001). The application of compost not only increased the exogenous C inputs but also promoted the transformation of CaCO3 to exchangeable Ca compared with the sole chemical fertilization. Furthermore, organic fertilization significantly increased the organic C in the heavy fraction (> 2.0 g cm−3) compared with the sole chemical fertilization, which was positively correlated with the mass proportion of macroaggregates (P < 0.001). These results indicate that organic fertilization can enhance the availability of Ca for C binding possibly by forming organo-Ca complexes, which in turn improve soil aggregation, and thus contribute to a long-term SOC sequestration in reclaimed soils of the Loess Plateau of China. •Exchangeable Ca was positively correlated with soil organic carbon (C).•CaCO3 was negatively correlated with the specific C mineralization rate.•Organic C in microaggregates was relatively stable.•The formation of organo-Ca complexes improved soil aggregation.•Organic fertilization promoted soil aggregation and enhanced C sequestration.